Chronic and acute ethanol impair the in vivo glucose uptake by lactating rat mammary gland. Issue 10 (October 1987) - Vilaró, S.; Viñas, O.; Herrera, E.; Remesar, X.
Abstract : Chronic and acute ethanol treatments increased the 3-hydroxybutyrate uptake by lactating rat mammary gland as a consequence of its high afferent concentration, without changing its relative extraction. The uptake of glucose was inhibited in the ethanol treated animals due to intrinsic alterations in the mammary gland metabolism as indicated by the decreased relative extraction and unchanged afferent concentration. These results would suggest that the elevated uptake of ketone bodies in ethanol-treated rats can be responsible, at least in part, for the decrease in glucose uptake by lactating rat mammary gland, although other direct effects of ethanol may be implied.